The Influence of Ethical Leadership and Organizational Commitment on Employee Performance - Yasin, Yasin; Herlambang, Toni; Sanosra, Abadi; Qomariah, Nurul (Budapest International Research and Critics University, 2024)
The Village Minimum Service Standards state that Village Government is the administration of government affairs and the interests of the local community, so public services by village officials are expected to be able to lead to good governance. The aim of this research was to have 2 (two) objectives, namely the first was to determine the influence of ethical leadership on the performance of village officials. The second objective is to determine the influence of organizational commitment on the performance of village officials. To obtain research data, a research questionnaire was used which was distributed to 100 village officials. The population is the Village Apparatus of Probolinggo Regency. The sample was determined as 100 respondents using random sampling technique. Validity and reliability tests were carried out so that the questionnaire could be used. The influence of the independent variable on the dependent variable was tested by testing the research hypothesis and the results were that ethical leadership and organizational commitment had a positive impact on employee performance in the Village Government in Probolinggo Regency.